A Report of a Case of Hyalinizing Trabecular Neoplasm of Thyroid Gland Associated With PAX8-GLIS3 Fusion. (21st September 2018) - Soliman, Mahmoud; Shevtsov, Artem; Zhao, Qing (Grace); Cerda, Sandra
Abstract: GLIS3 is a transcription factor indispensable for TSH/TSHR-dependent thyroid hormone biosynthesis and follicular cell proliferation. Likewise, PAX8 regulates the expression of genes encoding thyroglobulin, thyroid peroxidase, and the sodium-iodide symporter. Mutations of either PAX8 or GLIS3 have been associated with congenital hypothyroidism. Hyalinizing trabecular tumor of the thyroid gland is a peculiar variant of follicular cell–derived neoplasms, which shows characteristic trabecular arrangement and prominent hyaline feature. This entity has traditionally been linked to RET-PCT rearrangement. Here we report a case of hyalinizing trabecular tumor associated with PAX8-GLIS3 fusion. Reporting this novel association is crucial to further our understanding of the molecular underpinning of this pathological entity. A 62-year-old female complaining of a 2-cm midline thyroid mass underwent fine-needle aspiration. The Papanicolaou-stained direct smear showed a population of follicular cells with mild nuclear atypia and overlap in adenomatous and microfollicular patterns with a hemorrhagic background. The diagnosis of follicular lesion of undetermined significance (FLUS) (ie, Bethesda Category III) was rendered. Next-generation sequencing panel for thyroid cancer was performed revealing PAX8-GLIS3 fusion, a rare type of fusion that is expected, based on the available data, to confer 90% probability of cancer or noninvasive follicular thyroid neoplasm with papillary-like nuclear features (NIFTP). The risk of cancer recurrence associated with this fusion is not well defined. Surgical pathology examination of the total thyroidectomy specimen revealed a well-encapsulated tumor with histological features consistent with hyalinizing trabecular neoplasm measuring 1.9 cm in the pyramidal lobe without evidence of capsular or vascular invasion. In addition, two microcarcinomas (1 and 3 mm, respectively) of papillary thyroid carcinoma–follicular variant were identified, one in each of the right and left lobes. The background thyroid gland revealed multinodular goiter and chronic thyroiditis. No tumor was identified in six regional lymph nodes.